2018
DOI: 10.1186/s12885-018-4229-5
|View full text |Cite
|
Sign up to set email alerts
|

Germline breast cancer susceptibility gene mutations and breast cancer outcomes

Abstract: BackgroundIt is unclear whether germline breast cancer susceptibility gene mutations affect breast cancer related outcomes. We wanted to evaluate mutation patterns in 20 breast cancer susceptibility genes and correlate the mutations with clinical characteristics to determine the effects of these germline mutations on breast cancer prognosis.MethodsThe study cohort included 480 ethnic Chinese individuals in Taiwan with at least one of the six clinical risk factors for hereditary breast cancer: family history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 52 publications
4
52
1
5
Order By: Relevance
“…These results might be because we focused on a limited population of early-onset and TNBC patients. However, these findings have confirmed the results reported by Slattery et al 41 and Wang et al 42 Moreover, we evaluated the combination of BRCAness and FH. We found no overall significant association between the presence of BRCAness and a positive FH.…”
Section: Hitomi Mori Et Alsupporting
confidence: 91%
“…These results might be because we focused on a limited population of early-onset and TNBC patients. However, these findings have confirmed the results reported by Slattery et al 41 and Wang et al 42 Moreover, we evaluated the combination of BRCAness and FH. We found no overall significant association between the presence of BRCAness and a positive FH.…”
Section: Hitomi Mori Et Alsupporting
confidence: 91%
“…Furthermore, some genes were further verified by the identification between wild-type BC and normal tissue, which showed that a total of 43 genes had not only significant changes of expression level in BC patients but further more obvious changes in BRCA1/2-mutant BC patients. This demonstrated specific expression alternation of genes in our study, including TTK, EXO1, TICRR (TOBPPI interacting checkpoint and replication regulation) and so on, would be closely associated with BRCA1/2 mutations, providing a clue for further understanding the certain characteristic of BRCA1/2-mutant BC (for example, increased risk of distant metastasis and more aggressive nature) (Wang et al, 2018) and clarifying its pathogenesis.…”
Section: Discussionmentioning
confidence: 51%
“…The data in this regard are mixed, with a number of large metaanlayses demonstrating improved prognosis for patients with ovarian cancer harboring mutations in BRCA1/2 (79,80), possibly due to the relationship between BRCA1/2 mutations and platinum sensitivity. However, the data in patients with breast cancer are more mixed, with some studies indicating poorer prognosis in BRCA1/2-mutant patients (81,82).…”
Section: Fundamental Links Between Dna Damage Inflammation Cancer Pmentioning
confidence: 99%